Analisis Deskriptif Analitis Terhadap Kinerja Sistem Informasi Pelayanan Desa Berbasis SWOT di Desa Junjangan - Hary Wibowo; Abdullah; Muhammad Jibril (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
This study aims to determine the performance of a SWOT-based village service information system in Junjangan Village. The research method used was descriptive analytical with a qualitative approach. Data collection was conducted through observation, interviews, and documentation. Five respondents, consisting of operators and village officials, participated in the study.The research results show that the village service information system in Junjangan Village has helped improve the effectiveness of public administration services, expedited data processing, and simplified the storage of village documents. Based on the SWOT analysis, the strengths factor was 40%, opportunities 30%, weaknesses 20%, and threats 10%. The primary strength lies in the ease of administrative services and village data management. Weaknesses identified include limited operator capabilities and an unstable internet network. Opportunities for Junjangan Village include government support for village digitalization and information technology development. Threats identified include system disruptions, device damage, and low technological skills among some residents. Based on the research results, it can be concluded that the performance of the village service information system in Junjangan Village is quite good and effective in supporting village public services. However, improvements in the quality of human resources and technological infrastructure are needed to optimize village services.